Hitler's Ostkrieg and the Indian wars : comparing genocide and conquest - Westermann, Edward B. 1961- (Campaigns and commanders, 2016)
Visions of conquest: Manifest Destiny and Lebensraum -- National policies of race and space -- Strategy and warfare -- Massacre and atrocity -- War in the shadows: guerrilla warfare in the west and the east -- Conclusion